RELIGIOSITY IN COPING WITH PAIN, DEJECTION AND SOCIAL ISOLATION; A QUALITATIVE STUDY ON CANCER PATIENTS - Muhammad Asim; Sidra Saeed; Malik Muhammad Sohail et al. (Journal of University Medical & Dental College, 2017)
Abstract: With the beginning of scientific and technological advances religion has been ignored in clinical domain. However, empirical evidence shows that specific aspects of religiosity are correlated withhealth. This qualitative study covers aspects of religiosity and health in a way that has been ignored in studies conducted in Pakistan. Fifteen cancer patients were selectedthrough purposive sampling techniques that were getting cancer treatment from PINUM cancer hospital Faisalabad. Present study reveals that cancer patients consider religiosity as important mechanism in coping with pain, dejectionand social isolation. When they feel psychologically stable, it positively affects their ability to cope with disease. Findings suggest that religiosity is associated with better coping of patients with pain and dejection. Patients asserted that doctors generally do not pay attention towards religiosity of patients during treatment. Relationship of religiosity with hope in life has been described by many patients. Study has highlighted the need of doctor’s attention about religious and spiritual needs of cancer patients. Furthermore, this study has emphasized that patients want doctors to be attentive about their religious orientation. They want to talk about God and God related matters. These findings are significant for policy makers to understand palliative care of cancer patients.